Analisis Pengaruh Kemampuan, Motivasi Dan Kesempatan Terhadap Kinerja Pada Satuan Polisi Pamong Praja Kota Pontianak - Suparno Suparno; Aprina Kuswardani (STIE Widya Manggala, 2018)
This study aims to examine the effect of competency, motivation and opportunity on the performance of civil service police unit at Pontianak city. The samplewas 34 employees of civil service police unit. The type of data used is primary data. The data collected through questionnaire and analyzed by multiple linear regression. The result showed that competency and opportunities affect performance, while motivation does not affect performance.